Communication and Buen Vivir: the ALER experience (Revista Internacional de Folkcomunicação, 2021)
This article seeks to present reflections around the concept of Buen Vivir and its relation with people’s communication, as a response to the current systemic crisis and the capitalist model, taking as theoretical and practical example the Latin American Association of People’s Education and Communication (ALER). Based on literature review and interviews, this text raises discussions around Buen Vivir, which becomes more relevant with the New Latin American Constitutionalism; also on the debates around people’s communication and development models; and, finally, presents elements and formulations raise inside ALER, which has Buen Vivir as the central axis of its current political and communicational construction. Thus, it seeks to bring urgent and necessary reflections to think about new ways of living in society and communicational practices that reflect this demand. Buen Vivir; People’s communication; Latin American Association of People’s Education and Communication (ALER).